ANALISIS KUALITAS AIR DI PERAIRAN DANAU TOBA KECAMATAN PANGURURAN, KABUPATEN SAMOSIR - Silaban, Winarto; Silalahi, Mastiur Verawaty (JST (Jurnal Sains dan Teknologi), 2021)
Lake Toba is a lake located in Samosir Regency, North Sumatra Province with a surface area of 1,124 km2 (112,400 ha). Lake Toba is located at a geographical position 2°41′N 98°53′E / 2.68°N 98.88°E with an altitude of 995 above sea level. The purpose of this study was to determine water quality in terms of chemical, physical, and biological parameters, as well as the status of water quality in Lake Toba. Determination of the sample point using the "sample survey method" which is the method of taking the sample by dividing it into several segments or points that can represent the population. The method used in this study is a descriptive method with a quantitative approach. Based on the results of the study, it can be concluded that the quality of the waters of Lake Toba in Pangururan District is classified as not good, specifically nitrate, nitrite, and ammonia concentration. Those that are classified as good are temperature, pH, BOD5, O2, and COD. Water quality in Lake Toba is in the category of polluted lightly. Using biological analysis, Lake Toba waters in Pangururan District contain several phytoplankton, including Oocystis sp and Anabaena Sp.